Relationship between Family Support and Quality of Life in Stroke Patients - Zhachrani, Noer Fitri; Muchsin, Achmad Harun; Tammasesse, Jumraini (Newinera Publisher, 2024)
Stroke is a disease of the brain in the form of impaired local nerve function that appears suddenly, progressively, and quickly. Family support is very influential on stroke patients, because family support is very instrumental in a form of assistance provided by family members to provide physical and psychological comfort when someone experiences illness and provides social support. This article review aims to determine the relationship between family support and quality of life in stroke patients. This study used the literature review method with the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) protocol. Scientific articles or journals were downloaded from PubMed, Garuda Portal, and Google Scholar with SINTA IV and V standards within 2020-2024. In this literature, it was found that family support is an aspect that plays an important role in the quality of life of stroke patients. Family support itself includes emotional support, appreciation support, instrumental support and information support. The family is the closest person who always interacts with post-stroke patients, so the role of the family is very important in an effort to provide various supports that create a sense of security for patients.